Cocoon-Spinning Behavior and 20-Hydroxyecdysone Regulation of Fibroin Genes in Plutella xylostella - Shi, Yan; Lin, Gan-Lin; Fu, Xiu-Lian; Keller, Mike; Smagghe, Guy; Liu, Tong-Xian (Frontiers in Physiology, 2020)
The diamondback moth Plutella xylostella is a serious pest of crucifers. It has high reproductive potential and is resistant to many insecticides. Typically, the last-instar larvae of P. xylostella, before pupation, move to the lower or outer plant leaves to make a loose silk cocoon and pupate inside for adult formation. To better understand this pivotal stage we studied the cocoon-spinning behavior of P. xylostella and measured three successive phases by video-recording, namely the selection of a pupation site, spinning a loose cocoon and padding the scaffold cocoon. Subsequently, we cloned three fibroin genes related to cocoon production, i.e. fibroin light chain (Fib-L), fibroin heavy chain (Fib-H) and glycoprotein P25. A spatio-temporal study of these three fibroin genes confirmed a high expression in the silk glands during the final larval instar silk-producing stage. In parallel, we did an exogenous treatment of the insect molting hormone 20-hydroxyecdysone (20E), and this suppressed fibroin gene expression, reduced the normal time needed for cocoon spinning, and we also observed a looser cocoon structure under the scanning electron microscope. Hence, we demonstrated that the expression levels of key genes related to the synthesis of 20E (the three Halloween genes Spook (Spo), Shadow (Sad) and Shade (Shd)) decreased significantly during spinning, the expression of the 20E receptor (EcR and USP) was significantly lower during spinning than before spinning, and that the expression levels of CYP18-A1 related to 20E degradation were significantly up-regulated during spinning. The significance of the cocoon and the effects of 20E on the cocoon-spinning behavior of P. xylostella are discussed.